History of Criminal Justice Theory - Chapple, Constance L. (Handbook of forensic social work, 2024)
When tracing criminal justice theory development, it is wise to review its background in criminological thought. While criminal justice, as a separate academic discipline, emerged in the United States during Johnson’s Great Society, crime researchers and theorists have long been interested in the workings of the criminal justice system. The earliest writings in criminology by Beccaria, Bentham, and Hobbes address the criminal justice system’s operation exclusively. As criminology developed as a scholarly discipline within the United States, criminal justice practitioners often borrowed heavily from prevailing research and theory to design effective crime prevention and management policies. This chapter reviews the major paradigms of criminological thought and how they translate into criminal justice policy. The chapter concludes with a review of the major theories of criminal justice today.